An investigation on conjugated linoleic acid content, fatty acid composition, and physicochemical characteristics of Iranian Kurdish butter oil. Issue 2 (7th December 2022) - Faraji Sarabmirza, Rezgar; Joolaei Ahranjani, Parham; Rashidi, Ladan; Mousavi, Mohammad; Khodaiyan, Faramarz; Rashidi Nodeh, Hamid
Abstract: In this study, physicochemical and quality properties, fatty acid composition, and triglyceride composition of Iranian Kurdish butter oil (IKBO) obtained from yogurt drink (doogh) butter were investigated. Local doogh butter, prepared from cow's (CIKBO) and ewe's milk (EIKBO), was utilized as the raw material for this purpose. The free fatty acids (FFA) and peroxide values of IKBOs of the cow (CIKBO) and ewe (EIKBO) were obtained at 0.41 ± 0.01 and 0.39 ± 0.01 (g Oleic acid 100/g oil), and 1.32 ± 0.00 and 1.35 ± 0.00 (meq O2 kg/oil), respectively. The amounts of saturated fatty acids (SFAs): 70.27 ± 0.62 and 72.13 ± 0.84 (g/100 g), monounsaturated fatty acids (MUFAs): 19.37 ± 0.74 and 20.56 ± 0.97 (g/100 g), and polyunsaturated fatty acids (PUFAs): 1.22 ± 0.12 and 2.75 ± 0.38 (g/100 g) were obtained in CIKBO and EIKBO, respectively. The significant majority of the fatty acids (FAs) in the examined CIKBO and EIKBO were myristic (CIKBO: 13.76 ± 0.02 (g/100 g) and EIKBO: 14.83 ± 0.07 (g/100 g)), palmitic (CIKBO: 33.14 ± 0.28 (g 100/g) and EIKBO: 31.86 ± 0.02 (g/100 g)), stearic (CIKBO: 8.27 ± 0.06 (g/100 g) and EIKBO: 7.95 ± 0.06 (g/100 g)), capric (CIKBO: 4.83 ± 0.03 (g/100 g) and EIKBO: 6.75 ± 0.01 (g/100 g)), and oleic acids (CIKBO: 15.37 ± 0.12 (g/100 g) and EIKBO: 17.83 ± 0.02 (g/100 g)). The average of conjugated linoleic acid (CLA) content in EIKBO (2.20 ± 0.22 (g/100 g)) was higher than that in CIKBO (0.92 ± 0.25 (g/100 g)) ( p < .05). Therefore, EKIBO is considered the superior natural supply of CLA. Abstract : Local doogh butter was prepared from cow's (CIKBO) and ewe's milk (EIKBO). Then, the physicochemical properties, fatty acid composition, and triglyceride composition of CIKBO and EIKBO butter were investigated with gas chromatography (GC‐FID). Therefore, the GC‐FID profile is provided a superior natural supply of CLA and low molecular weight fatty acids.